Masson’s tumor of the breast in a patient with invasive breast carcinoma: a rare benign-vascular lesion mimicking malignancy - Resende, Cristiano Augusto Andrade de; Souto, Andreza Karine de Barros Almeida; Barbosa, Ana Carolina Silva; Roriz, Guilherme Dantas; Albuquerque, Gabriela Feitosa Lins de; Passos, Mauro Pinto; Basílio, Dunya Bachour (Mastology, 2026)
Introduction: Intravascular papillary endothelial hyperplasia (Masson’s tumor) is a rare benign vascular lesion, infrequently found in the breast. Its presentation can mimic malignancy on imaging and gross examination, posing a diagnostic challenge, particularly in oncologic patients. Objective: The aim was to report a rare case of a cavernous hemangioma (Masson’s tumor) associated with hematoma within the breast implant capsule, incidentally found during surgical treatment for recurrent invasive breast carcinoma. Methods: A descriptive case report was conducted of a patient diagnosed with recurrent invasive ductal carcinoma of the left breast associated with Masson’s tumor. Clinical, radiological, surgical, and histopathological data were collected and analyzed. Additionally, a narrative literature review was performed using databases such as PubMed and Scopus, focusing on previously reported cases of Masson’s tumor in the breast, particularly in association with implants or hematomas. Results: An 84-year-old post-menopausal woman with a history of left breast cancer presented with suspected local recurrence. Imaging revealed an additional intracapsular mass adjacent to the left breast implant. She underwent left breast segmentectomy and sentinel lymph node biopsy. Histopathological examination confirmed a 1.4×1.0×0.7 cm invasive ductal carcinoma, stage 1 (pT1c pN0(sn) M0), histologic grade 2, with clear surgical margins, and no lymph node involvement (0/3). Remarkably, a rare benign vascular lesion—cavernous hemangioma (Masson’s tumor)—associated with hematoma was concurrently identified within the implant capsule. The patient received adjuvant radiotherapy and is currently on aromatase inhibitor therapy, with no signs of recurrence to date. Conclusion: Masson’s tumor is a rare benign vascular lesion that can mimic malignancy, particularly in patients with a history of breast cancer. An incidental finding in this case highlighted the importance of thorough histopathological evaluation of periprosthetic lesions. Awareness of this entity is essential to avoid misdiagnosis and overtreatment.